2019
DOI: 10.4025/actascitechnol.v41i1.36402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an edible alginate coating with essential oil to improve the quality of a Fresh cheese

Abstract: This study focuses on an alginate edible coating with oregano and rosemary essential oils (EO) as well as its application in a Fresh cheese. The practical application was carried out by analyzing microbial contents, centesimal composition, texture (shear force) and instrumental color, sensory acceptance and mass loss. The coatings containing rosemary EO retained minimal numbers of Coliforms (35ºC) during storage; thus, a positive effect of the coatings on improving the microbiological cheese quality was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
4
5
0
2
Order By: Relevance
“…Pieretti et al studied the effect of the application of alginate edible coatings with oregano and rosemary essential oils on the texture of fresh cheese. At the beginning of the storage, they found that the uncoated sample presented the lowest hardness, proving to be softer than the coated cheese samples [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pieretti et al studied the effect of the application of alginate edible coatings with oregano and rosemary essential oils on the texture of fresh cheese. At the beginning of the storage, they found that the uncoated sample presented the lowest hardness, proving to be softer than the coated cheese samples [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…As alíquotas das soluções filmogênicas foram vertidas em placas com diâmetro de 9 cm e secas a 24°C por 24 horas (Fakhouri, 2007;Pieretti et al, 2019).…”
Section: Elaboração Das Coberturasunclassified
“…The project was approved by the Ethics and Research Committee -UEM, according to CAAE: 25081613.8.0000.0104. The acceptance index (IA) was also calculated by considering only the overall appearance attribute, equal to the average of each sample divided by the maximum grade, and multiplied by 100, according to Deolindo et al (2019) and Pieretti et al (2019).…”
Section: Cheeses Instrumental Color and Consumer Acceptabilitymentioning
confidence: 99%
“…Artisanal cheeses are important for regional development and family support in the interior of Brazil, but most producers of these foods are not aware of microbiological hazards and do not follow good manufacturing practices. As a result of this scenario, it is still frequently the case that microbiological analyzes of artisanal cheeses show high contamination and are outside acceptable hygienic-sanitary standards (Queiroz et al, 2017;Carvalho et al, 2019). Similar results to ours were observed in other studies regarding the microbiological quality of high or very high humidity cheeses.…”
Section: Microbiological Analysismentioning
confidence: 99%
See 1 more Smart Citation